PENGARUH KETERSEDIAAN JARINGAN KABEL (WIFI) TERHADAP AKSESIBILITAS PEMBELAJARAN DIGITAL BAGI SISWA SMPN SATAP 6 SIBULUE DI DESA MALLUSETASI - Muh. Fairul Arsal; Andi Suharman; A. Kasmawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of wired network (WiFi) availability on digital learning accessibility among students at SMPN Satap 6 Sibulue in Mallusetasi Village. The study employed a quantitative approach with an ex post facto design. The sample consisted of 49 students from Grades VIII and IX, selected using purposive sampling. Data were collected through questionnaires and documentation and were analyzed using descriptive statistics, prerequisite tests, and simple linear regression with the assistance of SPSS. The results showed that the data met the prerequisites for analysis, namely normal distribution, a linear relationship, and no indication of heteroscedasticity. The regression analysis produced the equation Y = 21.764 + 0.792X. The t-test showed that the t-value of 7.085 was greater than the t-table value of 1.677, with a significance value of 0.000 < 0.05, indicating that H1 was accepted. The R Square value of 0.516 indicates that the availability of a wired WiFi network explains 51.6% of the variation in digital learning accessibility, while the remaining 48.4% is explained by other factors outside the research model. Therefore, the availability of a wired WiFi network has a positive and significant effect on students’ digital learning accessibility.